Identifikasi Kawasan Potensial Untuk Penerapan Sistem Rainwater Harvesting (RWH) di Kota Palembang dengan Pendekatan Geographic Information System (GIS) - Imroatul Chalimah Juliana; Febrinasti Alia; M. Ichwanul Falah; Taufik Ari Gunawan (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2020)
Rainwater harvesting system (RWH) implementation may be a solution to maximize the water availability and reduce the runoff volume in Palembang City. For successful implementation, it is necessary to identify potential areas for RWH implementation. This study aims to identify areas in Palembang that are potential for implementing the RWH system. An analysis of parameters that affect the classification also conducted. This study used a geographic information system (GIS) approach using rainfall, slope, land use, and soil type parameters which are structured in a hierarchy using the analytical hierarchy process (AHP). Based on the weighted overlay method, it can be concluded that a very potential area for RWH implementation dominated with a wet area, flat slope, dense residential area and the type of soil which is not susceptible to infiltration. Whereas the medium and non-potential areas are dominated by steep and very steep slopes as well as unoccupied land use. Areas of high potential and potential reach 18.17% and 66.14% respectively. While the medium and not the potential is 13.66% and 2.03%. Areas of great potential are in the Buah, Kidul, Sekanak, Sriguna, Bendung, and Selinca Sub Watershed. Non-potential areas are only available in small area in DAS Gandus, Gasing, and Lambidaro Sub Watershed.